Pengembangan Media Pembelajaran Berbasis Web Google Sites Pada Materi Turunan Fungsi - husin saputra; Dina Octaria; Asnurul Isroqmi (Pendidikan Matematika Universitas PGRI Yogyakarta, 2022)
Google web sites are one of the media created by Google as development, the google web sites themselves are very suitable to be useful learning media because they are easy to operate and do not use coding in the process. The purpose was study develop mathematics learning media assisted by google sites on functional derivative materials that are valid, practical, and have potential effects. The research method used was Research and Development (R&D) with the ADDIE development model consisting of Analysis, Design, Development, Implementation, and Evaluation. The analyzed stage carried out by the researcher was needs analyze, curriculum analyze, media analyze. The design stage was designing products and device. The Development stage create media and performs validation. The Implementation stage conducts media trials to obtain practicality and potential effects. Evaluation stage, where the researcher discusses the value of practicality and potential effects. For data collection technique that researchers use, namely questionnaires, and learning outcomes tests. This research activity was carried out at SMA Negeri 15 Palembang with a total of 26 students. Keywords: ADDIE Model, Development, Google Web sites, Function Derivatives